Estudo da analogia de grelha no cálculo de lajes maciças de concreto armado - Col Debella, Leticia Barizon (2015)
For the study of the behaviour of massive slabs, several mathematical models have been proposed. These models are used to analyse the internal efforts and displacements due to shapes, boundary conditions and loads of taxes on the slabs. Among the processes that allow the consideration of the structure in its three-dimensional aspect, we highlight the process of grillage analogy that has as main idea the division of the slabs that make up the pavement in an appropriate number of bars, where the torsional and flexural rigidities of the slab are concentrated in these bars. This process lets you play a structural behavior of reality, and may close enough if you vary the geometry and the situations of structural arrangement. Unlike the grillage analogy, the analytical method through the tables of Bares adopts the structure decomposition into slabs and beams for the individual analysis of each element. This simplification may not translate correctly the behaviour of the structure. In this context, the present study were compared the values of maximum bending moments produced by the grillage analogy, using SAP2000 software, with those obtained using the tables of Bares. This comparison was applied to three different geometries of slabs: a massive slab square, a rectangle and a panel containing two slabs. Within the framework of the grillage analogy were tested hypotheses about the influence of mesh refinement, reducing the rigidity of torsion bars, and flexibility of the beams that serve as support for these slabs. Through these comparisons, was able to observe significant changes in values of bending moments, reinforcing the validation and the importance of this study.